MATRIMONY AS A BASIC POINT FOR SUBSTAINING THE STATE BY THE DOCTRINE OF REASON - Petrasovszky, Anna (European Integration Studies, 2017)
From the end of the 18th century, the most sophisticated version of Natural Law considered as the Kant type of Doctrine of Reason (School of Reason) was increasingly getting accepted in Hungarian Legal Philosophical Thinking. The expansion of initially “hated” Kantian thoughts started with a change of approach ongoing in Austria, when the Karl Anton Martini’s concept favored in royal circles was officially replaced by views of Franz Zeiller and Franz Egger accepting Kantian doctrine at the University of Vienna. This new critical theory of reason was firstly adopted within the Natural Law by Mihály Szibenliszt, so that he could give a way to such philosophers as inter alia Antal Virozsil, Imre Csatskó, István Bánó.